Pidgins and Creoles beyond Africa-Europe encounters - Buchstaller, Isabelle; Holmberg, Anders; Almoaily, Mohammad (Creole language library, 2014)
Evidence from Arabic-based pidgins, such as Bongor Arabic, Juba Arabic, Pidgin Madame, and Gulf Pidgin Arabic, and from the Arabic-based creole Ki-Nubi, shows that in these varieties verbs often derive from Arabic imperatives. In some of the West European-based pidgins, verbs apparently derive from infinitives in the lexifier. The difference may be explained by the morphology of the verb in the lexifier. In the communicative context of early pidginization, commands are frequent. These are normally expressed by an imperative, but in some languages, the infinitive may function as a directive and.